Adoption Process of IFRS for SMEs in Turkey: Insights from Academics and Accountants - Merve Kılıç; Ali Uyar (Journal of Accounting and Management Information Systems (JAMIS), 2017)
In 2009, the International Accounting Standards Board (IASB) issued International Financial Reporting Standards (IFRS) for Small and Medium-sized Entities (SMEs) as a simplified version of the full IFRS addressing the financial reporting needs of SMEs. Although IFRS for SMEs is still not required in this jurisdiction, Turkey was one of the first ones that have taken substantive steps towards adoption of IFRS for SMEs. The main purpose of this research is to investigate the perceptions of Turkish accountants, academicians, and auditors regarding the adoption process of IFRS for SMEs via in-depth interview methodology. The findings of the research confirmed the need for a stand-alone standard set for SMEs. The interviewees asserted that more simplification on IFRS for SMEs may hinder comparability of financial statements. While high-quality financial information will be the most important advantage of applying IFRS for SMEs, cost burdens on firms and lack of trained personnel will be the major obstacles for the implementation process.
Keywords: M41; M48; 650; IFRS for SMEs; SME; interviews; qualitative study; Turkey